#spirou4rights : a critical perspective on promoting human rights through comics. (2nd July 2020) - Reyns-Chikuma, Chris
ABSTRACT: Comics have been used for propaganda or for promoting different ideas by various institutions for a while. Spirou4Rights is an exhibition made of 17 panels with many one-page strips explaining the 30 articles of the Proclamation of the Human Rights sponsored by the UN available from 2018. This is not the first time the UN decided to use comic characters to promote a political ideal, sometimes provoking a backlash (e.g. Wonder Woman controversy in 2016). Taking advantage of the fact that this exhibition would celebrate two anniversaries at the same time (the 80th anniversary for Spirou—1938, and the 70th for the Declaration–1948), the UN surprisingly chose a character which, although cute, generous and courageous, is unknown outside the Francophone and maybe Francophile worlds. After presenting the interesting process through which this exhibition came out (context, dates, people involved, reasons for the choice) and acknowledging the good will of every participant, I will show how, these posters, the comic strips and the accompanying special issue of the magazine Spirou, are somehow problematic specifically in terms of ethnic and gender representations, reproducing the mentality of the out-of-touch 'Good Old White Boys' Club, ' not surprising in the rather gender-conservative BD world but quite shocking in the UN world.